A clinical review of obstetric hysterectomies done in medical college, Kottayam for a period of six years - Jayaram, Surya; Varghese, Acka Priya (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2016)
Background: Obstetric/peripartum hysterectomy is a hysterectomy performed for any indication during pregnancy, labour or puerperium. It is important to know the general incidence, changing trends and indications of this surgery. The objective of the study is to find out the incidence of obstetric hysterectomy, type of obstetric hysterectomy done, indications of the procedure, maternal clinical profile, postoperative complications and the maternal and fetal outcome. Methods: A retrospective, descriptive case series study of all pregnant women who underwent hysterectomy in a six year period has been done. Results: 57 women underwent hysterectomy. The incidence of obstetric hysterectomy in this study is 0.17%. Mean age of the women was 30.3 years. Mean parity was two. 1.75% of cases were unbooked. 24.56% of cases underwent obstetric hysterectomy following vaginal delivery and 74.44% of cases had the procedure following abdominal route of delivery. 56.14% of cases underwent obstetric hysterectomy for postpartum hemorrhage, 36.84% underwent it for morbidly adherent placenta. 90.47% of morbidly adherent placenta had previous caesarean section as a major risk factor. 12.3% of mothers died postoperatively. Conclusions: By good obstetric practices, proper diagnosis of morbidly adherent placenta, bringing down the number of unnecessary caesarean section the incidence of this procedure can be brought down.